PENGARUH STRUKTUR MODAL, UKURAN PERUSAHAAN DAN KEPEMILIKAN MANAJERIAL TERHADAP KINERJA PERUSAHAAN PADA PERUSAHAAN SEKTOR INDUSTRI BARANG KONSUMSI SUB SEKTOR MAKANAN DAN MINUMAN YANG TERDAFTAR DI BURSA EFEK INDONESIA (BEI) PERIODE TAHUN 2014-2017 - Hizkia Prasetya Panjaitan; Heru Cahyo; Tjahjani Murdijaningsih (FEB UNWIKU PURWOKERTO, 2020)
This study aims to analyze the effect of capital structure, company size and managerial ownership on company performance. This research was conducted at companies in the food and beverage sub-sector consumer goods industry which are listed on the Indonesia Stock Exchange (BEI) for the period 2014-2017. The number of samples used was 40 samples in 4 years. The sampling technique was using purposive sampling method. The analytical tool used in this study using multiple regression analysis using the SPSS 23 application. The t-test analysis conducted shows that the hypothesis for the capital structure variable is statistically accepted. This means that the increase in the company's capital structure will decrease the company's performance. Therefore, the company management must pay more attention and improve its capital structure in order to improve company performance. Meanwhile, the hypothesis for the variables of company size and managerial ownership was rejected statistically because the test results were not significant to company performance. Even so, it is better for companies to still consider company size and managerial ownership in order to improve company performance. One way that can be done to improve company performance is to perform periodic evaluation actions consistently related to the company's ability to generate profits from its total assets.